Dried distiller’s grains improve the performance of beef cattle intensively grazing early summer bluestem pasture - Epp, M.; Barnhardt, B.; Bryant, A.; Blasi, Dale A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Distiller’s grains are byproducts of the production of ethanol from grains and are an excellent source of protein and energy for cattle. The most prevalent use of distiller’s grains is in the finishing beef production sector. There is limited research available that has evaluated effectiveness of distiller’s grains as a supplement for grazing beef cattle. Digestible protein content in grass begins to decrease in midsummer, resulting in lower average daily gains. The objective of this study was to measure the daily gain of yearling steers supplemented with different levels of dried distiller’s grains while grazing doublestock Flint Hills pastures.
Keywords: Beef; Cattle; Dried distillers grain; Yearling steers